Variation in Nutritional and Antioxidant Attributes of Moringa oleifera L. Leaves at Different Maturity Stages - Qadir, Rahman; Anwar, Farooq; Bashir, Kiran; Tahir, Mudassir Hussain; Alhumade, Hesham; Mehmood, Tahir (Frontiers in Energy Research, 2022)
The present work reveals variation in nutritional and antioxidants profile of Moringa oleifera leaves with regard to four maturity stages (October to January). The percent yield and total phenolic contents (TPC) of 80% methanolic extract from M. oleifera leaves were found to be maximum (14.21 %, 95.26 mg/g) at early stage and minimum (9.695 %, 38.22 mg/g) at the later stage. Total flavonoids, ash, protein, vitamin C and β-carotene contents were found minimum at early stage and maximum at later stage (12.26 + 0.47 to 30.07 + 1.09 mg/g, 10.36% to 15.92% ,50.3 + 0.15 to 56 + 0.77 mg/g, 143.14 + 0.74 to 164.81 + 0.44 mg/100g, 89 + 0.28 to 112.8 + 1.40 mg/g). Amino acids including valine, alanine, leucine and phenylalanine were identified with their least contents at early stage (90.87, 53.07, 55.21, 48.65 mg/g) while maximum at later stage (197.66, 114.3, 114.2, 104.5 mg/g, respectively). The level of different minerals such as Cu, Fe, Mn in M.oleiefra leaves at different maturity stages varied from 0.59 to 2.08, 21.96 to 58.68, and 5.56 to 13.84 mg/100 g, respectively. RP-HPLC analysis of the nutritionally rich later stage leave samples, depicted the presence of quercetin as a major component (21.64 mg/kg) followed by benzoic acid, ferulic acid, sinapic acid, gallic acid, and p-coumaric acid with contribution at 13.03, 8.85, 3.39, 2.88, 1.59 mg/kg, respectively. Overall, a considerable variation in the profile of different nutrients and antioxidants was noted in M. oleifera leaves as maturity progressed. These results support harvesting of M. oleifera leaves at an appropriate maturity stage to maximize the functional food and nutraceutical benefits of this valuable food commodity.